2015
DOI: 10.18632/oncotarget.5676
|View full text |Cite
|
Sign up to set email alerts
|

miR-149 represses metastasis of hepatocellular carcinoma by targeting actin-regulatory proteins PPM1F

Abstract: microRNAs have been implicated in hepatocellular carcinoma (HCC) metastasis, which is predominant cause of high mortality in these patients. Although an increasing body of evidence indicates that miR-149 plays an important role in the growth and metastasis of multiple types of cancers, its role in the progression of HCC remains unknown. Here, we demonstrated that miR-149 was significantly down-regulated in HCC, which was correlated with distant metastasis and TNM stage with statistical significance. A survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 35 publications
2
61
1
Order By: Relevance
“…Fan et al (25) also reported that miR-149 promoted cell proliferation and suppressed apoptosis by mediating JunB in T-cell acute lymphoblastic leukemia. In addition, Luo et al (26) indicated that miR-149 repressed the metastasis of hepatocellular carcinoma by targeting protein phosphatase 1F, an actin-regulatory protein. Despite the existence of numerous studies investigating miR-149 in several tumors, the biological function and molecular mechanism of miR-149 in ovarian cancer remain unclear to date.…”
Section: Discussionmentioning
confidence: 99%
“…Fan et al (25) also reported that miR-149 promoted cell proliferation and suppressed apoptosis by mediating JunB in T-cell acute lymphoblastic leukemia. In addition, Luo et al (26) indicated that miR-149 repressed the metastasis of hepatocellular carcinoma by targeting protein phosphatase 1F, an actin-regulatory protein. Despite the existence of numerous studies investigating miR-149 in several tumors, the biological function and molecular mechanism of miR-149 in ovarian cancer remain unclear to date.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the overexpression of miR-149 suppressed the migration and invasion of HCC by targeting protein phosphatase, Mg 2+ /Mn 2+ dependent 1F directly (35). miR-148a induces hepatocytic differentiation by inhibiting the inhibitor of nuclear factor κα/NUMB/NOTCH pathway (36).…”
Section: Discussionmentioning
confidence: 99%
“…5A, B). Previous studies showed that PPM1F was a direct target of miR-149 in HCC [20]. We also identified PPM1F as a potential target of miR-149 based on its mirSVR score (−1.277) and PhastCons score (0.602) by using microRNA.org (http://www.microrna.org/).…”
Section: Silencing Snhg8 Counteracted the Tumor-promoting Effects Of mentioning
confidence: 99%
“…Previously, miR-149 has been demonstrated to function as a tumor suppressor in multiple malignant tumors [20,[28][29][30]. It suppresses cell proliferation and invasion by targeting FOXM1 in CRC [28], GIT1 in breast cancer [29], and ZBTB2 in GC [30].…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andmentioning
confidence: 99%